(untitled) (Research, Society and Development, 2022)
This study aimed to identify the nursing care provided to the newborn in the context of the COVID-19 pandemic. This is an integrative literature review, conducted through six databases, from February to April 2021. The descriptors newborn, nursing care, nursing, coronavirus infection, COVID-19 were used. A total of 1,355 articles were identified, which were imported to the rayyan platform. After analysis, 11 were selected and three categories of care were defined: care for the newborn; Care for the mother/family; Care of health professionals. Because of the facts mentioned, it was realized that providing care in the hospital environment with newborns was challenging for nurses and other health professionals involved in the care of the mother-child binomial, due to the context of the COVID-19 pandemic.